The Influence of the Purification Method on the Molecular Mass and Hydrodynamic Behaviors of Apple Pectin - Zumratov, Azizbek Kh.; Nasriddinov, Abubakr S.; Kholov, Shavkat E.; Ismoilov, Ikromjon B.; Ashurov, Ashurboy I.; Muhidinov, Zayniddin K.; Khalikov, Djurabay Kh. (Fine Chemical Engineering, 2025)
This study investigates the influence of purification methods on the molecular weight and hydrodynamic properties of pectin polysaccharides (PPs) obtained from apple pomace using the flash hydrolysis method. PPs were purified from the hydrolysate solution through alcohol precipitation (AP) and dia-ultrafiltration (DUF). The molecular weight and molecular weight distribution (MWD) were analyzed using high-performance size exclusion liquid chromatography (HPLC) equipped with an online differential refractometer and viscometer. Hydrodynamic parameters, including intrinsic viscosity ([η]) and hydrodynamic radius (Rh (w)), were determined using the ASTRA 5.3.4.20 software. The application of the DUF method during hydrolysate purification yielded superior molecular parameters, with the polydispersity coefficient (Mw/Mn) decreasing by nearly half. Additionally, increased DUF cycles significantly improved [η] and Rh (w) values from 92.7 to 107.7 g/mL and from 9.7 to 11.0 nm, respectively. The Mw-Rh (w) plot suggests that pectin polysaccharide (PP) macromolecules predominantly exhibit shapes resembling segmented rods or swollen coils, with slopes of 0.65 and 0.64 for both purified samples. The combined double-cycle ultrafiltration and ethanol precipitation process, using an optimal pectin solution-to-ethanol (EtOH) ratio of 1:2, emerged as a more effective purification strategy. This approach enhances the molecular weight and hydrodynamic properties of pectin, which are essential for various applications. Furthermore, the DUF method reduces the reliance on large quantities of expensive, flammable alcohol and eliminates the need for vacuum evaporation, resulting in a cost-effective, sustainable, and environmentally friendly pectin production process.